10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundIsolated pulmonary light-chain deposition disease (LCDD) is a rare presentation of monoclonal immunoglobulin deposition disease and is histologically characterized as Congo red-negative amorphous tissue deposits in the lung.PresentationA 73-year-old woman with a history of IgG-kappa chronic lymphocytic leukemia (CLL), not requiring therapeutic management, presented with unintentional weight loss, night sweats, and flushing. Positron emission tomography/computed tomography (PET/CT) scan showed a 1-cm fluorodeoxyglucose (FDG)-avid nodule in the right lower lobe of the lung. She underwent wedge resection, which showed a lymphoplasmacytic infiltrate with associated deposits of dense eosinophilic material that mass spectrometry revealed to consist of kappa immunoglobulin light chains. Flow cytometry and IGH clonality analysis detected a small kappa-restricted lymphocytic population with only a few minor clones overlapping with the patient's CLL-associated clone, indicating minimal involvement of CLL and possible other etiologies of immunoglobulin overproduction and tissue deposition.DiscussionThis case report highlights the importance of accurate diagnosis of pulmonary LCDD, such that patients are monitored for lung dysfunction and assessed for systemic disease involvement, which can significantly impact mortality and morbidity in affected individuals.